Method for preparing block alpha-HgS nonlinear optical crystal through CVT technology cyclic heat treatment and application of block alpha-HgS nonlinear optical crystal
Through CVT technology, the temperature cycle is controlled using NH4Cl and I2 as transport agents, and the temperature cycle is solved, the temperature and pressure control problems of preparing α-HgS crystals in the prior art are achieved, high-quality and low-cost preparation is achieved, and nonlinear optical response performance is improved.
Patent Information
- Application Number
- CN202411665479.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-28
AI Technical Summary
It is difficult to effectively prepare high-quality α-HgS nonlinear optical crystals in the prior art, and the temperature and pressure need to be strictly controlled during the preparation process, and there are vacancy and defect problems.
The CVT technology cycle heat treatment method is used to perform secondary growth through chemical vapor phase transport method, and NH4Cl and I2 are used as transport agents to control the temperature cycle at the source and deposition ends, and gradually improve the quality and size of the crystals.
It realizes the preparation of high-quality millimeter-level α-HgS nonlinear optical crystals under mild conditions, reducing energy consumption and reaction costs, avoiding vacancy and defect problems, and improving the nonlinear optical response performance of the crystals.
Smart Images

Figure CN119710932A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of crystal material growth, and specifically relates to a method for preparing a bulk alpha-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology and an application thereof. Background Art
[0002] α-HgS is a chalcogenide nonlinear optical crystal. Nonlinear optics is the science of studying nonlinear phenomena produced when light interacts with matter. It has a wide range of applications in laser technology, optical communications, optical information processing, photonics, and other fields. At present, the infrared nonlinear optical crystals widely used in business are AgGaS2, AgGaSe2, and ZnGeP2, but they all have disadvantages such as low laser damage threshold and strong two-photon absorption. Therefore, it is of great significance to explore infrared nonlinear optical crystals with excellent comprehensive performance. In addition, binary chalcogenide compounds have the advantages of simple structure and convenient synthesis compared to ternary and higher compounds.
[0003] Relevant researchers in this field have used mercuric chloride (HgCl2) as a mercury source, sodium sulfide nonahydrate (Na2S·9H2O) as a sulfur source, and deionized water as a solvent to hydrothermally synthesize rhombohedral α-HgS crystals. The above method requires strict control of reaction temperature and pressure. The phase transition temperature of α-HgS is between 315 and 330°C. Excessively high temperature will cause HgS to transform from red α-HgS to black β-HgS. In addition, the micron and nanocrystals obtained by this method have a large number of vacancies and defects. The physical properties of the material cannot be accurately characterized based on the powder material, and the practical application of powder in nonlinear optics is relatively limited.
[0004] It can be seen that it is of great value to develop a method for preparing high-quality α-HgS crystals with mild preparation conditions, low cost, simple and efficient preparation. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing bulk α-HgS nonlinear optical crystals by cyclic heat treatment using CVT technology and its application, and adopts a secondary growth chemical vapor transport method to prepare millimeter-level α-HgS single crystals by cyclic heat treatment.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions: A bulk α-HgS nonlinear optical crystal is a bulk mercury sulfide single crystal with a chemical formula of HgS. The crystal belongs to the trigonal system, the P3221 point group, and the lattice parameters are: a=b=4.149Å, c=9.495Å, c / a=2.289, α=β=90°, and γ=120°.
[0007] The present invention also provides a method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment of CVT technology, using HgS powder as raw material, NH4Cl and I2 as transport agents, and growing α-HgS small grains once by chemical vapor transport cyclic heat treatment; During the first growth, the source end is heated to 380-420°C and kept warm for 360-480 minutes, then cooled to 180-220°C and kept warm for 240-360 minutes, and then heated to 380-420°C. The above procedure is repeated 6 times and then cooled to room temperature; the deposition end is heated to 265-305°C and kept warm until the source end cycle is completed, and then cooled to room temperature together with the source end.
[0008] Based on the above technical solution, the present invention can also be improved as follows.
[0009] Furthermore, the above-mentioned method of preparing bulk α-HgS nonlinear optical crystals by CVT technology cyclic heat treatment is based on the primary growth of small α-HgS grains, and continues the secondary growth by chemical vapor transport cyclic heat treatment to obtain millimeter-level bulk α-HgS nonlinear optical crystals.
[0010] Furthermore, in the above-mentioned method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment of CVT technology, HgS powder, NH4Cl and I2 are added into a clean quartz tube respectively; the quartz tube is placed in liquid nitrogen and cooled for 2-3 minutes, and then vacuum is drawn under the continuous freezing environment of liquid nitrogen to a pressure of 10 -2 Pa, and finally the quartz tube is sealed with a hydrogen-oxygen flame, and then another growth is carried out.
[0011] Furthermore, in the above-mentioned method of preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment of CVT technology, the HgS powder, NH4Cl and I2 are placed in a quartz tube, and the quartz tube must be kept clean. The cleaning method is: after soaking it with detergent, ultrasonic washing with acetone and ethanol reagents in turn for 0.5-2h, then rinsing with deionized water for 0.5-1h, and finally drying it.
[0012] Furthermore, in the above-mentioned method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment of CVT technology, the quartz tube is evacuated to an internal pressure of less than 10 -4 Pa.
[0013] Furthermore, in the above-mentioned method of preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment of CVT technology, the conditions for secondary growth are: the source end is heated to 380-420℃ and kept warm for 360-480min, then cooled to 180-220℃ and kept warm for 240-360min, then heated to 380-420℃, the above procedure is cycled 6 times and then cooled to room temperature; the deposition end is heated to 265-305℃ and kept warm until the source end cycle is completed, and then cooled to room temperature together with the source end.
[0014] Furthermore, in the above-mentioned method of preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology, after the primary growth and secondary growth are completed, the source end and deposition end of the quartz tube are slowly cooled, and the cooling rate of the source end and the deposition end is 0.5-1°C / min.
[0015] Furthermore, in the above-mentioned method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology, the length of the quartz tube is 23-25 cm, and the inner diameter is about 13-15 mm.
[0016] Furthermore, in the above-mentioned method of preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology, the molar ratio is HgS:NH4Cl:I2=36:4:1.
[0017] A bulk α-HgS nonlinear optical crystal prepared by any of the above methods is used as a frequency doubling crystal in the infrared band.
[0018] Furthermore, the intensity of the second harmonic of the frequency doubling crystal used in the infrared band is positively correlated with the power of the incident laser at different laser frequencies of 840nm, and reaches the highest at 140mW, which can withstand a maximum of 9.17×10 5 W / cm 2 The pulsed laser intensity.
[0019] The beneficial effects achieved by one or more embodiments of the present invention are as follows: After adding HgS powder, a certain amount of NH4Cl powder and I2 powder still need to be added to the quartz tube as a reaction transport agent. The present invention uses NH4Cl and I2 as transport agents, and the effect of using NH4Cl and I2 together is better than that of using I2 alone. Due to the temperature oscillation at the source end, the cyclic mass transfer process of the transport agent will generate a by-product Hg3S2I2-xClx on the crystal surface, and the transport agent will be exhausted. Usually, a shorter oscillation period is used to reduce the formation of by-products. Here, we add NH4Cl to help suppress the changes in temperature and composition caused by steam convection on the crystal growth surface, thereby reducing defects and vacancies caused by steam convection.
[0020] To prevent I2 from volatilizing, it must first be frozen in liquid nitrogen and kept frozen during the vacuum process. After vacuuming, the quartz tube must be sealed.
[0021] Due to the presence of a large number of vacancies and defects in the micro / nano particles, as well as a large interface ratio, the α-HgS single crystal obtained by secondary growth in the present invention can effectively avoid the above situation. In addition, the reaction temperature of the method is low, which can effectively reduce energy consumption. At the same time, it is carried out under vacuum conditions, which can reduce the requirements for equipment compared with the prior art, thereby reducing the reaction cost.
[0022] The millimeter-scale α-HgS that has undergone secondary growth can be used to test the bulk second harmonic effect. The second harmonic response intensity increases linearly under different laser frequencies of 840nm, which has good practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Comparison of images of α-HgS crystals after one growth in Example 1 and two growths in Example 2 for the raw material of the same quartz tube of the present invention. (a) is an image of α-HgS crystals grown once in Example 1, and (b) is an image of α-HgS crystals grown twice in Example 2.
[0024] Figure 2 The following are pictures of crystals taken out from the reaction container after growth according to the present invention, wherein (a) is a picture of the α-HgS single crystal sample after secondary growth, and (b) is a picture of the α-HgS crystal sample in Comparative Example 2.
[0025] Figure 3 This is a comparison of the pictures of the same quartz tube of the present invention after secondary growth and tertiary growth in Example 5, where (a) is secondary growth and (b) is tertiary growth.
[0026] Figure 4 It is a comparison chart of the spectrum of the α-HgS sample in Example 1 measured by an X-ray diffractometer for the powder of the present invention and the theoretical value spectrum (obtained from the database of the Jede software).
[0027] Figure 5 It is a schematic diagram of the structure of the α-HgS crystal obtained in the present invention.
[0028] Figure 6 This is a diagram of the second harmonic effect of the α-HgS crystal obtained in the present invention under 840nm laser irradiation with different powers. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but the content of the present invention is not limited to the following embodiments.
[0030] A bulk α-HgS nonlinear optical crystal is a bulk mercury sulfide single crystal with a chemical formula of HgS. The crystal belongs to the trigonal system, the P3221 point group, and the lattice parameters are: a=b=4.149Å, c=9.495Å, c / a=2.289, α=β=90°, and γ=120°.
[0031] The present invention also provides a method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment of CVT technology, using HgS powder as raw material, NH4Cl and I2 as transport agents, and growing α-HgS small grains once by chemical vapor transport cyclic heat treatment; During the first growth, the source end is heated to 380-420°C and kept warm for 360-480 minutes, then cooled to 180-220°C and kept warm for 240-360 minutes, and then heated to 380-420°C. The above procedure is repeated 6 times and then cooled to room temperature; the deposition end is heated to 265-305°C and kept warm until the source end cycle is completed, and then cooled to room temperature together with the source end.
[0032] Furthermore, the above-mentioned method of preparing bulk α-HgS nonlinear optical crystals by CVT technology cyclic heat treatment is based on the primary growth of small α-HgS grains, and continues the secondary growth by chemical vapor transport cyclic heat treatment to obtain millimeter-level bulk α-HgS nonlinear optical crystals. Furthermore, in the above-mentioned method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment of CVT technology, HgS powder, NH4Cl and I2 are added into a clean quartz tube respectively; the quartz tube is placed in liquid nitrogen and cooled for 2 minutes, and then vacuum is drawn under the continuous freezing environment of liquid nitrogen to a pressure of 10 -2 Pa, and finally the quartz tube is sealed with a hydrogen-oxygen flame, and then another growth is carried out.
[0033] Furthermore, in the above-mentioned method of preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment of CVT technology, the HgS powder, NH4Cl and I2 are placed in a quartz tube, and the quartz tube must be kept clean. The cleaning method is: after soaking it with detergent, ultrasonic washing with acetone and ethanol reagents in turn for 0.5-2h, then rinsing with deionized water for 0.5-1h, and finally drying it.
[0034] Furthermore, in the above-mentioned method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment of CVT technology, the quartz tube is evacuated to an internal pressure of less than 10 -4 Pa.
[0035] Furthermore, in the above-mentioned method of preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment of CVT technology, the conditions for secondary growth are: the source end is heated to 400°C and kept warm for 420 minutes, then cooled to 200°C and kept warm for 300 minutes, and then heated to 400°C, and the above procedure is cycled 6 times before cooling to room temperature; the deposition end is heated to 285°C and kept warm until the source end cycle is completed, and then cooled to room temperature together with the source end.
[0036] Furthermore, in the above-mentioned method of preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology, after the primary growth and secondary growth are completed, the source end and deposition end of the quartz tube are slowly cooled, and the cooling rate of the source end and the deposition end is 0.5-1°C / min.
[0037] Furthermore, in the above-mentioned method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology, the length of the quartz tube is 23-25 cm, and the inner diameter is about 13-15 mm.
[0038] Furthermore, in the above-mentioned method of preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology, the molar ratio is HgS:NH4Cl:I2=36:4:1.
[0039] A bulk α-HgS nonlinear optical crystal prepared by any of the above methods is used as a frequency doubling crystal in the infrared band.
[0040] Furthermore, the intensity of the second harmonic of the frequency doubling crystal used in the infrared band is positively correlated with the power of the incident laser at different laser frequencies of 840nm, and reaches the highest at 140mW, which can withstand a maximum of 9.17×10 5 W / cm 2 The pulsed laser intensity.
[0041] The growth principle of primary α-HgS crystal: the raw material is placed at the source end, and NH4Cl and I2 are used as the transport medium to transport HgS powder from the source end to the deposition end for growth. When the HgS concentration reaches the saturation point, small crystal nuclei will spontaneously form. The α-HgS crystal is recrystallized through chemical vapor transport cycle treatment, and secondary growth is carried out to obtain α-HgS single crystal.
[0042] The growth principle of secondary α-HgS crystals: the temperature at the source end cycles between high and low. When the temperature at the source end increases, the small α-HgS impurity crystals at the deposition end will be decomposed. When the temperature at the source end decreases, these impurity crystals will be transported to the source end and become the raw materials for secondary growth again. After this process continues for a period of time, a certain amount of crystals will still be retained at the deposition end as nucleation points for secondary growth.
[0043] The following is an exemplary description of the method for preparing the α-HgS crystal provided by the present invention. Example 1 First, the quartz tube was thoroughly cleaned by ultrasonic cleaning in acetone and ethanol reagents for 1 h, respectively, and then rinsed with deionized water several times. Finally, the quartz tube was completely dried to obtain a clean quartz tube.
[0044] Next, add HgS powder (2 g), NH4Cl and I2 (60 mg each) into a clean quartz tube. Place the quartz tube in liquid nitrogen and cool for 2 min. Then, evacuate the tube under continuous freezing of liquid nitrogen to a pressure of 10 -2 Pa. Finally, the quartz tube (about 23 cm long and 13 mm in diameter) was sealed with a hydrogen-oxygen flame.
[0045] Finally, the sealed quartz tube was placed in a tube furnace with two independently controlled heating ends (one for the source end and the other for the deposition end). The temperature control settings for the crystal growth process were as follows: First, the temperature of the source end and the deposition end was raised from room temperature to 400°C and 285°C over 360 minutes, and kept at a constant temperature for 420 minutes; second, the source end was cooled from 400°C to 200°C over 200 minutes and kept at a constant temperature for 300 minutes; third, the source end was raised from 200°C to 400°C over 200 minutes, and the temperature of the deposition end was maintained at 285°C during this process. This process was repeated 6 times and then cooled to room temperature to end one growth. The resulting crystals were as follows: Figure 1 As shown in (a), Figure 5 It is a schematic diagram of the structure of the α-HgS crystal obtained in the present invention.
[0046] The ground α-HgS crystals were subjected to XRD test (such as Figure 4 ) confirmed the phase purity of the samples.
[0047] Comparative Example 1 This comparative example is basically the same as Example 1, except that the temperature of the deposition end is adjusted to 265° C., as follows.
[0048] First, the quartz tube was thoroughly cleaned by ultrasonic cleaning in acetone and ethanol reagents for 1 h, respectively, and then rinsed with deionized water several times. Finally, the quartz tube was completely dried to obtain a clean quartz tube.
[0049] Next, add HgS powder (2 g), NH4Cl and I2 (60 mg each) into a clean quartz tube. Place the quartz tube in liquid nitrogen and cool for 2 min. Then, evacuate the tube under continuous freezing of liquid nitrogen to a pressure of 10 -2 Pa. Finally, the quartz tube (about 23 cm long and 13 mm in diameter) was sealed with a hydrogen-oxygen flame.
[0050] Finally, the sealed quartz tube is placed in a tubular furnace with two individually controlled heating ends (as the source end and the deposition end, respectively). The temperature control setting of the crystal growth process: First, the temperature of the source end and the deposition end is first raised from room temperature to 400°C and 265°C after 360 minutes, and the temperature is kept constant for 420 minutes; second, the source end is cooled from 400°C to 200°C after 200 minutes and the temperature is kept constant for 300 minutes; third, the source end is heated from 200°C to 400°C after 200 minutes, and the temperature of the deposition end is maintained at 265°C during this process. After the process is cycled 6 times, it is cooled to room temperature to end one growth. Compared with Example 1, the temperature of the deposition end is reduced, the red α-HgS growth interval moves to the right, the length of the red α-HgS interval in the tube is shortened, and the yield decreases.
[0051] Comparative Example 2 This comparative example is basically the same as Example 1, except that the temperature of the deposition end is adjusted to 295° C., as follows.
[0052] First, the quartz tube was thoroughly cleaned by ultrasonic cleaning in acetone and ethanol reagents for 1 h, respectively, and then rinsed with deionized water several times. Finally, the quartz tube was completely dried to obtain a clean quartz tube.
[0053] Next, add HgS powder (2 g), NH4Cl and I2 (60 mg each) into a clean quartz tube. Place the quartz tube in liquid nitrogen and cool for 2 min. Then, evacuate the tube under continuous freezing of liquid nitrogen to a pressure of 10 -2 Pa. Finally, the quartz tube (about 23 cm long and 13 mm in diameter) was sealed with a hydrogen-oxygen flame.
[0054] Finally, place the sealed quartz tube into a tubular furnace with two separately controlled heating ends (as the source end and the deposition end respectively). The temperature control settings of the crystal growth process: First, the temperature of the source end and the deposition end is first increased from room temperature to 400°C and 295°C after 360 minutes, and maintained at a constant temperature for 420 minutes; second, the source end is cooled from 400°C to 200°C after 200 minutes and maintained at a constant temperature for 300 minutes; third, the source end is heated from 200°C to 400°C after 200 minutes, and the temperature of the deposition end is maintained at 295°C during this process. This process is repeated 6 times and then cooled to room temperature, ending one growth. Compared with Example 1, black crystals will be attached to the red crystals grown in the tube this time, such as Figure 2 (b).
[0055] Comparative Example 3 This comparative example is basically the same as Example 1, except that the temperature of the deposition end is adjusted to 305° C., as follows.
[0056] First, the quartz tube was thoroughly cleaned by ultrasonic cleaning in acetone and ethanol reagents for 1 h, respectively, and then rinsed with deionized water several times. Finally, the quartz tube was completely dried to obtain a clean quartz tube.
[0057] Next, add HgS powder (2 g), NH4Cl and I2 (60 mg each) into a clean quartz tube. Place the quartz tube in liquid nitrogen and cool for 2 min. Then, evacuate the tube under continuous freezing of liquid nitrogen to a pressure of 10 -2 Pa. Finally, the quartz tube (about 23 cm long and 13 mm in diameter) was sealed with a hydrogen-oxygen flame.
[0058] Finally, the sealed quartz tube is placed in a tubular furnace with two separately controlled heating (as the source end and the deposition end respectively). The temperature control setting of the crystal growth process: First, the temperature of the source end and the deposition end is first raised from room temperature to 400°C and 305°C after 360 minutes, and the temperature is kept constant for 420 minutes; second, the source end is cooled from 400°C to 200°C after 200 minutes and the temperature is kept constant for 300 minutes; third, the source end is heated from 200°C to 400°C after 200 minutes, and the temperature of the deposition end is maintained at 305°C during this process. After the process is cycled 6 times, it is cooled to room temperature to end one growth. Compared with Example 1, the red crystals grown in the tube are connected to the black crystal intervals, and it is difficult to separate them later.
[0059] Comparative Example 4 This comparative example is substantially the same as Example 1, except that no NH4Cl is added to the raw materials.
[0060] First, the quartz tube was thoroughly cleaned by ultrasonic cleaning in acetone and ethanol reagents for 1 h, respectively, and then rinsed with deionized water several times. Finally, the quartz tube was completely dried to obtain a clean quartz tube.
[0061] Next, add HgS powder (2 g) and I2 (60 mg) into a clean quartz tube. Place the quartz tube in liquid nitrogen and cool for 2 min. Then, evacuate the tube under continuous freezing of liquid nitrogen to a pressure of 10 -2 Pa. Finally, the quartz tube (about 23 cm long and 13 mm in diameter) was sealed with a hydrogen-oxygen flame.
[0062] Finally, the sealed quartz tube is placed in a tubular furnace with two individually controlled heating ends (as the source end and the deposition end respectively). The temperature control setting of the crystal growth process: First, the temperature of the source end and the deposition end is first raised from room temperature to 400°C and 285°C after 360 minutes, and the temperature is kept constant for 420 minutes; second, the source end is cooled from 400°C to 200°C after 200 minutes and the temperature is kept constant for 300 minutes; third, the source end is heated from 200°C to 400°C after 200 minutes, and the temperature of the deposition end is maintained at 285°C during this process. After the process is cycled 6 times, it is cooled to room temperature to end one growth. Compared with Example 1, the mass transfer process in the tube is significantly reduced, the red crystals at the deposition end are reduced, and the quality is reduced.
[0063] Example 2 Based on the crystal grown in Example 1, the α-HgS single crystal was grown again using the chemical vapor transport cyclic heat treatment method: The quartz tube that has undergone crystal growth once is put back into the tube furnace for crystal regrowth. The temperature control settings for crystal growth are as follows: First, the temperature of the source end and the deposition end is first raised from room temperature to 400°C and 285°C over 360 minutes, and kept at a constant temperature for 420 minutes; second, the source end is cooled from 400°C to 200°C over 200 minutes and kept at a constant temperature for 300 minutes; third, the source end is heated from 200°C to 400°C over 200 minutes, and the temperature of the deposition end is maintained at 285°C during this process. This process is cycled 6 times and then cooled to room temperature to end the secondary growth.
[0064] like Figure 1 The crystal changes after primary and secondary growth of the raw material in the same sealed quartz tube are shown. Compared with the primary growth, the crystal quality is greatly improved after the secondary growth, the number of crystals increases, and the size becomes larger. After taking out the crystals of primary growth and secondary growth and measuring the size, it is found that Figure 1 (a) Figure 1 As shown in (b), the secondary growth of α-HgS crystal is more than doubled compared to the primary growth, and the crystal quality is significantly improved. This process is repeated many times, and the secondary crystal growth can effectively improve the crystal quality and size.
[0065] Example 3 This embodiment is basically the same as embodiment 2, except that the temperature control settings for the primary growth and secondary growth of the crystal are: first, the temperature of the source end and the deposition end is first increased from room temperature to 380°C and 265°C after 360 minutes, and maintained at a constant temperature for 360 minutes; second, the source end is cooled from 380°C to 180°C after 200 minutes and maintained at a constant temperature for 240 minutes; third, the source end is heated from 180°C to 380°C after 200 minutes, during which the temperature of the deposition end is maintained at 180°C. This process is repeated 6 times and then cooled to room temperature to end the secondary growth.
[0066] Example 4 This embodiment is basically the same as embodiment 2, except that the temperature control settings for the primary growth and secondary growth of the crystal are: first, the temperature of the source end and the deposition end is first increased from room temperature to 420°C and 305°C after 480 minutes, and maintained at a constant temperature for 480 minutes; second, the source end is cooled from 420°C to 220°C after 200 minutes and maintained at a constant temperature for 360 minutes; third, the source end is heated from 220°C to 420°C after 200 minutes, during which the temperature of the deposition end is maintained at 305°C. The process is repeated 6 times and then cooled to room temperature to end the secondary growth.
[0067] Example 5 This example is based on the crystal grown in Example 1, and the temperature of the deposition end is adjusted to study the phase change process of red α-HgS and black β-HgS.
[0068] The quartz tube that has undergone crystal growth once is put back into the tube furnace for crystal regrowth. Temperature control settings for crystal growth: The temperature setting at the source end is the same as in Example 2. The temperature at the deposition end is adjusted to 275°C. After the growth is completed, compared with the red crystal in Example 2, it is found that the area of the red crystal on the tube wall increases as follows: Figure 3 (a). We speculate that due to the decrease in temperature at the deposition end, a portion of the black crystals transformed into red crystals.
[0069] Next, we put the quartz tube after secondary growth into the tube furnace for the third growth. Temperature control settings for crystal growth: The temperature setting at the source end is the same as that for secondary growth. The temperature at the deposition end is adjusted to 295°C. After the growth is completed, compared with the secondary growth red crystal, the area of the red crystal on the tube wall is reduced as follows: Figure 3 (b). This verifies our hypothesis that there is a reversible phase transition between red crystals and black crystals. By controlling the temperature, the temperature change during the mass transfer process can promote the reversible transformation of black β-HgS to red α-HgS.
[0070] In summary, the crystals obtained under the conditions of Example 2 have the best quality.
[0071] Application Example 1 In this application example, the α-HgS single crystal obtained in Example 2 is placed under 840nm laser irradiation to perform second harmonic response tests at different powers.
[0072] First, the quartz tube was cleaned according to the steps of Example 1, and HgS (3 g), NH4Cl and I2 (60 mg each) were added to the clean quartz tube. Then, the quartz tube was sealed according to the steps of Example 1.
[0073] Secondly, the sealed quartz tube is placed in a tube furnace. The temperature control settings of the crystal growth process are as follows: First, the temperature of the source end and the deposition end is first raised from room temperature to 400°C and 285°C over 360 minutes, and the temperature is maintained at a constant temperature for 420 minutes; second, the source end is cooled from 400°C to 200°C over 200 minutes and the temperature is maintained at a constant temperature for 300 minutes; third, the source end is heated from 200°C to 400°C over 200 minutes, and the temperature of the deposition end is maintained at 285°C during this process. This process is cycled 6 times and then cooled to room temperature to end one growth.
[0074] Based on the crystal grown once, the α-HgS single crystal is grown again using the chemical vapor transport cyclic heat treatment method.
[0075] The quartz tube that has undergone one crystal growth is put back into the furnace for crystal regrowth. The temperature control settings of the crystal growth process are: first, the temperature of the source end and the deposition end is first increased from room temperature to 400℃ and 285℃ after 360min, and maintained at a constant temperature for 420min; second, the source end is cooled from 400℃ to 200℃ after 200min and maintained at a constant temperature for 300min; third, the source end is heated from 200℃ to 400℃ after 200min, and the temperature of the deposition end is maintained at 285℃ during this process. This process is repeated 6 times and then cooled to room temperature to end the secondary growth.
[0076] The α-HgS single crystal obtained by the present invention was placed under 840nm laser irradiation to conduct second harmonic response tests of different powers. The results are as follows: Figure 6 As shown in the figure, with the increase of laser power, the second harmonic effect of α-HgS single crystal also increases. The intensity of the second harmonic is positively correlated with the power of the incident laser, and reaches the highest at 140mW, and can withstand a maximum of 9.17×10 5 W / cm 2 The slope of the straight line obtained by fitting the experimental data is 1.836, which proves that the α-HgS single crystal has an excellent laser damage threshold.
[0077] It can be seen that the α-HgS single crystal prepared by the present invention has an effective nonlinear optical response, and its performance can be regulated by laser power, and can be used as a frequency conversion crystal for near-infrared detectors.
[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A bulk α-HgS nonlinear optical crystal, characterized in that: It is a bulk mercury sulfide single crystal with the chemical formula HgS. The crystal belongs to the trigonal system, P3221 point group, and the lattice parameters are: a=b=4.149Å, c=9.495Å, c / a=2.289, α=β=90°, γ=120°.
2. A method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology, characterized in that: Using HgS powder as raw material, NH4Cl and I2 as transport agents, α-HgS small grains were grown once by chemical vapor transport cyclic heat treatment; During the first growth, the source end is heated to 380-420°C and kept warm for 360-480 minutes, then cooled to 180-220°C and kept warm for 240-360 minutes, and then heated to 380-420°C. The above procedure is repeated 6 times and then cooled to room temperature; the deposition end is heated to 265-305°C and kept warm until the source end cycle is completed, and then cooled to room temperature together with the source end.
3. The method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology according to claim 2, characterized in that: Based on the primary growth of small α-HgS grains, the secondary growth is continued by chemical vapor transport cyclic heat treatment method to obtain millimeter-scale bulk α-HgS nonlinear optical crystals.
4. The method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology according to claim 2, characterized in that: Add HgS powder, NH4Cl and I2 into a clean quartz tube respectively; cool the quartz tube in liquid nitrogen for 2-3 minutes, and then evacuate the tube under continuous freezing of liquid nitrogen to a pressure of 10 -2 Pa, and finally the quartz tube is sealed with a hydrogen-oxygen flame, and then another growth is carried out.
5. The method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology according to claim 4, characterized in that: The HgS powder, NH4Cl and I2 are placed in a quartz tube, and the quartz tube must be kept clean. The cleaning method is: soak it in detergent, then ultrasonically wash it with acetone and ethanol reagents in turn for 0.5-2 hours, then rinse it with deionized water for 0.5-1 hour, and finally dry it.
6. The method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology according to claim 4, characterized in that: The quartz tube was evacuated to a pressure lower than 10 -4 Pa.
7. The method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology according to claim 4, characterized in that: The conditions for the secondary growth are: the source end is heated to 380-420°C and kept warm for 360-480 minutes, then cooled to 180-220°C and kept warm for 240-360 minutes, then heated to 380-420°C, the above procedure is cycled 6 times and then cooled to room temperature; the deposition end is heated to 265-305°C and kept warm until the source end cycle is completed, and then cooled to room temperature together with the source end.
8. The method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology according to claim 7, characterized in that: After the primary growth and the secondary growth are completed, the source end and the deposition end of the quartz tube are slowly cooled, and the cooling rate of the source end and the deposition end is 0.5-1°C / min.
9. The method for preparing bulk α-HgS nonlinear optical crystal by cyclic heat treatment using CVT technology according to any one of claims 2 to 8, characterized in that: The length of the quartz tube is 23-25 cm, and the inner diameter is 13-15 mm.
10. A bulk α-HgS nonlinear optical crystal obtained by the preparation method according to any one of claims 4 to 8, used as a frequency doubling crystal in the infrared band.
Citation Information
Cited By
Method for preparing HgS crystal by controlling crystal form through wet recrystallization
CN120191958A